Hidden in Plain Sight?: The Case of the Invisible Queer Womanist Biblical Scholar - Lovelace, Vanessa (Biblical theology bulletin, 2024)
This article explores the politics of respectability, representation, and the intersection of academic womanist and queer hermeneutics of the Bible. As early as the nineteenth century, U.S. born-Black women have had to contend with race and gender prejudice to secure their rightful place in society. Too often this came at the cost of respectability politics. Middle class Black church women advocated for the adoption of a strict code of behavior by Black women in order to advance their agenda of respectability in society. I am interested in whether the politics of respectability both within the church and academy have contributed to the essential invisibility of LGBTIAQ2+-identified womanist biblical scholars or womanist scholarship using a queer hermeneutical approach. Have the male heteropatriarchy and biblical authority in the church and academy effectively silenced womanist LGBTI/queer scholarship? This article suggests that while this may have been true of the past, the closet doors are opening and a growing number of womanist scholars are embracing LGBTI/queer methodological approaches in biblical interpretation.